Carious lesion activity assessment in clinical practice: a systematic review (2019)
Objectives The objective of the manuscript is to systematically review the different techniques developed for activity assessment of coronal carious lesions (AACCL) in clinical settings. Materials and methods A search of PubMed identified original articles in English reporting on the different concepts/tools for AACCL in clinical settings and, when available, data related to their in vivo/in situ validation in terms of sensitivity, specificity, inter- and intra-examiner reproducibilities, area under the receiving operating curve, positive predictive value, negative predictive value, and relative risk of lesion progression. Results The present review included 25 articles. Four groups of techniques are available (1) systems based on combinations of visual and tactile criteria; devices based on (2) pH assessment, (3) fluorescence, or (4) bioluminescence. The most studied systems are those based on combinations of visual and tactile parameters when bioluminescence suffers from the lack of in vivo evaluation. Validation studies showed a wide disparity among protocols in terms of populations, dentitions, teeth surfaces, study design, the gold standard, and validation criteria. Conclusion There is a need for definition and harmonization of standards for activity assessment-related concepts/tools, as well as further investigations for in vivo validation of newly developed tools. Clinical relevance Carious lesion activity is an important component to be taken into account when making decisions as to appropriate clinical caries management. The development and use of validated techniques which are easy to use in everyday dental practice are important.